NOMINATION PROCESSES AND ERGONYM RESEARCH - Xudaybergenova Umida Komildjanovna; Matniyozova Gulizebo Adilbekovna (TADQIQOTLAR, 2026)
Abstract. This article examines the linguistic characteristics of the Russian- speaking population and the sociocultural foundations of the nomination process through the prism of linguocultural studies, one of the most relevant fields of contemporary linguistics. The research provides a comprehensive analysis not only of the principles underlying the formation of onomastic units but also of their relationship with human cognition and national mentality. Furthermore, the communicative and pragmatic potential of ergonyms, as well as their role in modern advertising and marketing systems, are substantiated from a scientific perspective.